Damage and Stability Analysis of Sandstone-Type Uranium Ore Body under Physical and Chemical Action of Leaching Solution - Liu, Yulong; Huang, Lei; He, Guicheng; Hu, Nan; Zhou, Shuhui; Yu, Qing; Ding, Dexin (Archives of mining sciences = Archiwum górnictwa, 2023)
In this paper, the typical sand-conglomerate uranium ore in north China was taken as the research object. The uniaxial compression and tensile tests of sand-conglomerate specimens under natural status and acidic solution status were used to research the compressive strength, tensile strength, Young’s modulus, cohesion and internal friction angle. Focusing on this type of uranium deposit, during the underground design of the in-situ leaching mining method, the three-dimensional finite element method was used to conduct a numerical simulation of the liquid collecting tunnel with different structural parameters of 10 m×2 m, 3 m×2 m, 2 m×2 m, and comprehensively analyse the vertical displacement, principal stress and plastic deformation zone changes of the tunnelbefore and after leaching. Based on the results, influenced by an acidic aqueous solution, the grain of the conglomerate became soft and secondary pores appeared, resulting in the superimposed effect of physical damage and chemical damage. Macroscopically, an obvious decrease was witnessed in mechanical property. Based on the stability and economy factor of three scenarios before and after leaching, the scenario was recommended as the experimental testing scenario, specifically, two longitudinal collecting tunnel were arranged along the strike of the orebody, with the size of 3 m×2 m and the width of the middle pillar of 4 m. The results of the numerical simulation are significant in guiding the design of underground in-situ leaching technology and determining the structural parameters of the deposit.